BIRTH AND DEVELOPMENT OF PHRASEOLOGY AS A LINGUISTIC DISCIPLINE IN WORLD LINGUISTICS - Adaxamjonova. M.B; Abduvaliyev M.A (Galaxy International Interdisciplinary Research Journal, 2022)
The present article is devoted to the study of the stages of history and development of phraseology in world linguistics, which contains culture-related information . It was divided into several periods according to Soviet, modern Russian and foreign scientists. They transmit significant information about the range of issues that arose during the study of typology of praseological dictionaries. The theoretical part of this article deals with the problems of recording phrases and idioms in dictionaries. The investigation of the development phrases in phraseology helps to identify the specifics of understanding phraseology, history of phraseological dictionaries, and their use nowadays in world linguistics.